Teaching wave-particle complementarity using the Virtual Mach-Zehnder Interferometer - Cavalcanti,C J H (2020)
We propose the teaching of wave-particle duality mediated by a software called Virtual Mach-Zehnder Interferometer, developed by our research group. We introduce the Dirac’s formalism contextualized on the Mach-Zehnder Interferometer, constructing explicitly the operators that represent the action of each device on the interferometer, calculating probability amplitudes on screens. Wave-particle complementarity is explored both in the qualitative and quantitative perspective, using computational simulations provided by the software. By studying concepts such as visibility, predictability and distinguishability, we explore the intermediate interference patterns aiming to expand what has not traditionally been found in textbooks and most courses. With the purpose of illustrating the application of the software in the classroom, the paper presents some didactical situations experienced by students of a physics teacher-training course during a quantum physics class, discussing students’ discursive interactions. The didactical approach to quantum interference phenomena carried out with the software, whether qualitative or quantitative, can promote rich and interesting discussions among students, exploring recent topics of quantum physics and allowing them to have a deeper and articulated understanding of the theory.